Magnetic field mediated conductance oscillation in graphene p–n junctions. (27th March 2018) - Cheng, Shu-Guang
Abstract: The electronic transport of graphene p–n junctions under perpendicular magnetic field is investigated in theory. Under low magnetic field, the transport is determined by the resonant tunneling of Landau levels and conductance versus magnetic field shows a Shubnikov–de Haas oscillation. At higher magnetic field, the p–n junction subjected to the quasi-classical regime and the formation of snake states results in periodical backscattering and transmission as magnetic field varies. The conductance oscillation pattern is mediated both by magnetic field and the carrier concentration on bipolar regions. For medium magnetic field between above two regimes, the combined contributions of resonant tunneling, snake states oscillation and Aharanov–Bohm interference induce irregular oscillation of conductance. At very high magnetic field, the system is subjected to quantum Hall regime. Under disorder, the quantum tunneling at low magnetic field is slightly affected and the oscillation of snake states at higher magnetic field is suppressed. In the quantum Hall regime, the conductance is a constant as predicted by the mixture rule.